Sensor a fibra ótica nanoestruturado e funcionalizado para aplicação em ambientes hídricos - Heidemann, Bárbara Rutyna (2016)
This work shows optical fiber transducers based on long period gratings (LPG), modified with nanostructures to achieve optimized performance. The cladding of the fiber with the previously recorded grating was coated with gold nanoparticles (AuNPs), by functionalizing its surface with 3-aminopropyltriethoxysilane, further recoated with tetrachloroauric acid solution and sodium borohydride reduction. The localized surface plasmon resonance (LSPR) on the AuNPs was excited by its coupling with LPG transmission modes. Such device was projected aiming to increase its sensitivity, particularly in water environments. A 17-times increased sensitivity was obtained for this LPG modified with gold nanoparticles (LPG-AuNPs) intensity coded, when compared with the non-modified transducer, for refractive indices close to 1.3933. Resulting resolutions were as small as 0.0003 RIU (refractive index units), within the range from 1.3629 to 1.4399. For the LPG-AuNPs wavelength coded, higher sensitivities were obtained for refractive indices close to the water refractive index, as well as a limit resolution of 0.00001 RIU in environments with refractive indices close to the fiber cladding refractive index. However, this device was not able to detect small changes in concentration of analytes in water solution. A further chemical modification of the AuNPs was carried out by functionalization with cysteamine. The LPG-AuNPs was inserted in a cysteamine hydrochloride aqueous solution, and the transducer selectivity was assessed for water solutions of glyphosate in the 1 μM to 100 μM concentration range. For the latter transducer configuration, changes of 0.6 % and 0.34 nm were obtained for intensity coded and wavelength coded operation, respectively, showing the prospect of selective detection of traces of analytes in water environments.